2022
DOI: 10.3389/fpsyg.2022.862897
|View full text |Cite
|
Sign up to set email alerts
|

Social Wellbeing, Board-Gender Diversity, and Financial Performance: Evidence From Chinese Fintech Companies

Abstract: The main goal of this study is to investigate the relationship between female representation on board of directors and financial performance, using evidence from Chinese fintech companies, which are providing financial services using cutting-edge technologies. This research used fintech firms listed on the Shanghai and Shenzen Stock Exchange from 2010 to 2019 to test the research questions using regression analyses by SPSS v26. According to the data, the Blau index has a large and negative influence on Tobin's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Two major perspectives have emerged at these levels of analysis, a social categorization perspective and an information/decision-making perspective (Köllen, 2021;van Knippenberg et al, 2004). The empirical work has resulted in GM 38,8 positive, negative and nonsignificant impacts within each perspective (Ghafoor et al, 2022;Moon and Christensen, 2020;Pandey et al, 2022;van Knippenberg et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Two major perspectives have emerged at these levels of analysis, a social categorization perspective and an information/decision-making perspective (Köllen, 2021;van Knippenberg et al, 2004). The empirical work has resulted in GM 38,8 positive, negative and nonsignificant impacts within each perspective (Ghafoor et al, 2022;Moon and Christensen, 2020;Pandey et al, 2022;van Knippenberg et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In line with this stream of thinking, race and gender have often been used in diversity research as proxies for differences in perspectives and human capital (Hillman et al , 2002; Kolev and McNamara, 2020; Roh and Sung, 2022). However, despite their long histories as variables of interest, their effects have been inconsistent within the research (An and Lee, 2022; Hoobler et al , 2018; Makkonen, 2022; Riordan, 2000), even as their salience and importance in business have increased (Ghafoor et al , 2022; Miller and Triana, 2009; Verhulst and DeCenzo, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of WBoC serves as a control function (Assenga, Aly & Hussainey, 2018;Lafuente & Vaillant, 2019) and monitoring function (Rahman & Zahid, 2021;Zhou, Owusu-Ansah & Maggina, 2018) to improve firm performance (FP) (Mubarka & Kammerlander, 2022;Ramadan & Hassan, 2022). While empirical research on the influence of WBoC on FP has shown inconclusive results, many studies have shown that the presence of WBoC either has a lower impact on FP (Adams & Ferreira, 2009;Akpan & Amran, 2014;Darmadi, 2013;Fauzi & Locke, 2012;Ghafoor, Duffour, Khan & Khan, 2022;Mubarka & Kammerlander, 2022;Roudaki, 2018) or a positive impact on FP (Dissanayake, Jeyaraj & Nerur, 2021;Mubarka & Kammerlander, 2022;Ramadan & Hassan, 2022;Tran, Nguyen& Wang, 2022). Meanwhile, other studies (Hatane, Winoto, Tarigan & Jie, 2022;Kumar, Nigam & Singh, 2020;Shukeri, Shin & Shaari, 2012;Wang, Abbasi, Babajide & Yekini, 2019) have also shown that the presence of WBoC has no impact on FP.…”
Section: Introductionmentioning
confidence: 99%
“…Does family ownership moderate the influence of the existence of women board of commissioners on firm performance? Studies on WBoC and FP have been extensively conducted in developed countries such as Italy (Flabbi, Macis, Moro & Schivardi, 2019), Iceland (Gudjonsson, Kristinsson, Gylfason & Minelgaite, 2020), Germany (Green & Homroy, 2017), Spain (Valls-Martínez & Cruz-Rambaud, 2019, Britain (Gong & Girma, 2021), and China (Ghafoor et al, 2022). However, researchers have yet to explore the relationship between WBoC and FP moderated by FO in developing countries.…”
Section: Introductionmentioning
confidence: 99%